Characterization of laser-produced plasmas as light sources for extreme ultraviolet lithography and beyond - Yin, Liang, author; Rocca, Jorge J., advisor; Menoni, Carmen S., committee member; Marconi, Mario C., committee member; Yalin, Azer, committee member (Colorado State University. Libraries, 2019)
Lithography is a critical process in the fabrication of integrated circuits. The continuous increase in computing power for more than half a century has depended in the ability to print smaller and smaller features, which has required the use of light sources operating at increasingly shorter wavelengths. There is keen interest in the development of high-power light sources for extreme ultraviolet (EUV) lithography at λ=13.5 nm and future beyond extreme ultraviolet (BEUV) lithography near λ=6.7 nm. The work conducted in this dissertation has characterized aspects of laser-produced plasmas (LPPs) that serve as light sources for EUV / BEUV lithography. The laser pulse shape dependence of the conversion efficiency of λ=1.03 μm laser into in-band 13.5 nm EUV emission in a Sn LPP was studied as a function of laser pulse shape and durations. Laser pulses of arbitrary temporal shape with variable energy and pulse widths were generated using a programmable pulse synthesizer based on a diode-pumped chirped pulse amplification Yb: YAG laser. The pulse synthesizer is based on wave front splitting and pulse stacking for the generation of arbitrary shape laser pulses of Joule-level energy. Pulses ranging from hundreds of ps to several ns were generated with a single laser. The measurements showed the CE favors the use of nearly square pulses of duration longer than 2 ns, in agreement with hydrodynamic/atomic physics simulations. A significant increase in CE was observed when Q-switched pulses were substituted by square pulses of similar duration. Conditions were observed at which the EUV pulse duration significantly outlasts the laser pulse in the direction normal to the target surface, in contrast at grazing angles the measured EUV pulse duration is shorter and similar to the laser pulse duration. The physics leading to this angular anisotropy is discussed, along with the spectroscopic characterization of EUV emission and at-wavelength images that characterize the source size. Another aspect of this dissertation includes a comprehensive study of the emission from Gd and Tb LPPs in the λ=6.5 - 6.7 nm region. BEUV emission spectra were measured as a function of laser pulse duration (120 ps - 4 ns), emission angle, and spatial location within the plasma. At-wavelength images of the BEUV emitting plasma region were obtained as a function of irradiation parameters. The peak of the emission spectrum was observed to broaden and to shift to longer wavelengths as the laser pulses are shortened from ns to hundreds of ps. Transient self-consistent hydrodynamic/atomic physics simulations show that the picosecond irradiation creates significantly hotter plasmas in which the dominant emission originates from more highly ionized species. Gd LPP emission driven by nanosecond laser pulses best matched the reflectivity band of our La/B4C mirrors. Spatially resolved spectra of the Gd LPP were acquired for different laser parameters and were compared to simulations. The CE into in-band BEUV emission was determined by integrating angularly resolved measurements obtained using an array of calibrated energy monitors. A maximum CE of 0.47% / 0.45% for the Gd / Tb LPPs was obtained within a 0.6% bandwidth. The results are of potential interest BEUV lithography.
Keywords: conversion efficiency; lithography; plasma; EUV; characterization; photonics